A Common Marking Technique Affects Tadpole Behavior and Risk of Predation. (27th December 2012) - Carlson, Bradley E.; Langkilde, Tracy; Foster, S.
Abstract In many studies, it is necessary for researchers to mark individual animals for later identification. It is often assumed in the interpretation of these studies that marks have no effects on the biology of the animals. This assumption is insufficiently tested, and, when it is, coarse assessments of negative effects are often used, such as survival and growth under simplified laboratory conditions. We examined the consequences of a common larval amphibian marking technique (staining with methylene blue) for wood frog tadpole behavior and survival in an ecologically realistic scenario (predation). We measured a number of tadpole behavioral variables, under baseline conditions and in the presence of olfactory cues of a predator, for marked and unmarked tadpoles. We then exposed pairs of tadpoles (one marked and one unmarked) to one of two predators and tested for the effects of marking on the susceptibility of tadpoles to predation. We found that marking suppressed the increase in movement rate that typically occurred in (unmarked) tadpoles in the presence of predator cues. Marked tadpoles were significantly more likely to be captured by predators, an effect that could not be attributed to this difference in movement rate. These results raise concern about the use of this staining method and highlight the need for studies involving marked animals to thoroughly address any relevant effects the marks may have on the biology of the subjects.